Current Topics in Caesarean Section - Tsikouras, Panagiotis; Nikolettos, Nikolaos; Rath, Werner; Friedrich Von Tempelhoff, Georg (IntechOpen, 2021)
In 2019, approximately 1.2 million caesarean sections were performed in the United States, accounting for 31.7% of all births that year. In most European countries, the rate of caesarean delivery also exceeds 30%. The medical effects of this phenomenon remain unclear.This book presents comprehensive information on caesarean delivery including the risks and benefits, clinical indications, scientific guidelines, and more.